Clinical Spectrum and Management of Ovarian Masses in Children and Adolescent up to 20 Years of Age (Bangladesh Medical Journal, 2021)
Pathological type as well as management of ovarian tumor in the pediatric population are different than adult women. We performed a retrospective analysis of clinical and diagnostic aspects of ovarian tumors and tumor-like lesions in girls in order to identify characteristics associated with malignancy and it’s clinical management which is different from adult women. This is a descriptive type of cross sectional study was condunted among  seventy nine female  children and adolescent  admitted in Bangabandhu Sheikh Mujib Medical University (BSMMU) with ovarian mass from January 2017 to December 2020.  Secondary data were collected from hospital record review. The demographic data, diagnostic procedure, management and histopathological analysis of the ovarian tumor were recorded. Mean age of study population was 16.7±3.1 and age range was 8-20 Years. Benign and malignant ovarian tumor was 40.50% and 59.49% respectively. The main symptom and sign were abdominal pain and palpable mass were found in 51% and 50% cases respectively. Malignant lesion appeared as cystic in 22.44%, solid 44.89% and mixed in 32.65% cases. But benign   ovarian tumor was found predominantly as cystic in 70% cases preoperatively. More than three fourth (75.51%) of malignant ovarian tumor showed one or more positive tumor marker whereas one third (33.33%) benign tumor had raised tumor marker. Large lesions in both benign and malignant cases were found in almost similar number of cases and these were 80% and 81% respectively. In the group of solid tumors, positive tumor marker results occurred more frequently in patients with malignant tumor (57.14%). Elevated serum alpha feto protein (AFP), Human Chorionic Gonadotrophin (HCG) and high Lactate Dehydrogenage (LDH) value associated more often with malignant tumor. Laparotomy was performed in all cases of study population.  Among 49 malignant ovarian tumour 34 (69.3%) underwent ovary preserving surgery. All patient with benign ovarian tumor undergone conservative surgery. Predominantly solid structures noted on imaging studies, large dimension and positive tumor markers are clinical predictors of malignancy. Multicenter prospective studies are needed to improve and unify the ovarian preservation rates across the world.Bangladesh Med J. 2021 January; 50(1) : 1-9